2018
DOI: 10.1002/jcp.28000
|View full text |Cite
|
Sign up to set email alerts
|

AdoMet triggers apoptosis in head and neck squamous cancer by inducing ER stress and potentiates cell sensitivity to cisplatin

Abstract: S‐Adenosyl‐l‐methionine (AdoMet) is a naturally and widely occurring sulfonium compound that plays a primary role in cell metabolism and acts as the principal methyl donor in many methylation reactions. AdoMet also exhibits antiproliferative and proapoptotic activities in different cancer cells. However, the molecular mechanisms underlying the effects exerted by AdoMet have only been partially studied. In the current study, we evaluated the antiproliferative effect of AdoMet on Cal‐33 oral and JHU‐SCC‐011 lary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…In a previous study by the authors, to the best of our knowledge, the mechanisms underlying the antitumor effect of AdoMet on HNSCC were reported for the first time, demonstrating that AdoMet was able to induce apoptosis, involving a caspase-dependent mechanism paralleled by an increased Bax/Bcl-2 ratio in Cal-33 and JHU-SCC-011 cells following 48 and 72 h of treatment, respectively (13).…”
Section: Effects Of Adomet On the Apoptosis Of Cal-33 And Jhu-scc-011mentioning
confidence: 85%
See 4 more Smart Citations
“…In a previous study by the authors, to the best of our knowledge, the mechanisms underlying the antitumor effect of AdoMet on HNSCC were reported for the first time, demonstrating that AdoMet was able to induce apoptosis, involving a caspase-dependent mechanism paralleled by an increased Bax/Bcl-2 ratio in Cal-33 and JHU-SCC-011 cells following 48 and 72 h of treatment, respectively (13).…”
Section: Effects Of Adomet On the Apoptosis Of Cal-33 And Jhu-scc-011mentioning
confidence: 85%
“…In a previous study by the authors, the synergistic effect of AdoMet in association with cDDP, an agent commonly used in cancer therapy, in inhibiting Cal-33 cell proliferation and in enhancing cell apoptosis, was demonstrated (13). It was found that the optimal combination of the two drugs, highly synergistic with the CalcuSyn calculation, corresponded to 200 µM AdoMet and 0.18 µM cDDP following 72 h of treatment.…”
Section: Adomet Synergistically Enhances the Cddp-induced Inhibition mentioning
confidence: 93%
See 3 more Smart Citations